The Relationship between Menstrual Patterns and Pain Scale in Endometriosis Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Fatimah Usman; Megan Reginia Rusli; Eka Handayani Oktharina; Kemas Yusuf Effendi; Syifa Alkaf (HM Publisher, 2023)
Background: Endometriosis is a disease characterized by the presence of tissue resembling the endometrium (uterine lining) outside the uterus. This causes a chronic inflammatory reaction that can result in the formation of scar tissue in the pelvis and other parts of the body. Pain is the most common clinical complaint in cases of endometriosis. Pain during menstruation is often confused with pain due to endometriosis, so treatment delays often occur. This study aimed to determine the relationship between menstrual patterns and pain in endometriosis patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This was cross-sectional analytic observational study. A total of 55 research subjects participated in this study. Data analysis was carried out with the help of SPSS version 25 software in univariate and bivariate. Results: Menstrual cycle, duration, color, and volume of menstrual blood are not related to pain intensity in endometriosis patients. Conclusion: There is no relationship between menstrual patterns and pain in endometriosis patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.